Incidence, Predictors, and Outcomes of Implantable Cardioverter‐Defibrillator Discharge Among People Living With HIV. Issue 18 (18th September 2018) - Alvi, Raza M.; Neilan, Anne M.; Tariq, Noor; Awadalla, Magid; Rokicki, Adam; Hassan, Malek; Afshar, Maryam; Mulligan, Connor P.; Triant, Virginia A.; Zanni, Markella V.; Neilan, Tomas G.
Abstract : Background: People living with HIV (PHIV) are at an increased risk for sudden cardiac death, and implantable cardioverter‐defibrillators (ICDs) prevent SCD. There are no data on the incidence, predictors, and effects of ICD therapies among PHIV. Methods and Results: We compared ICD discharge rates between 59 PHIV and 267 uninfected controls. For PHIV, we tested the association of traditional cardiovascular risk factors and HIV‐specific parameters with an ICD discharge and then tested whether an ICD discharge among PHIV was associated with cardiovascular mortality or an admission for heart failure. The indication for ICD insertion was similar among groups. Compared with controls, PHIV with an ICD were more likely to have coronary artery disease and to use cocaine. In follow‐up, PHIV had a higher ICD discharge rate (39% versus 20%; P =0.001; median follow‐up period, 19 months). Among PHIV, cocaine use, coronary artery disease, QRS duration, and higher New York Heart Association class were associated with an ICD discharge. An ICD discharge had a prognostic effect, with a subsequent 1.7‐fold increase in heart failure admission and a 2‐fold increase in cardiovascular mortality, an effect consistent across racial/ethnic and sex categories. Conclusions: ICD discharge rates are higher among PHIV compared with uninfected controls. Among PHIV, cocaine use and New York Heart Association class are associated with increased ICD discharge, and an ICD discharge is associated with a subsequent increase in admission for heart failure and cardiovascular mortality.